The “Old Soldier’s” Panegyrics to the Young Monarch in Russian and Swedish Literatures of the 18th Century - Mikhail Y. Ljustrov (Studia Litterarum)
The article examines one of the forms of European panegyric — an appeal to the monarch who has just ascended to the throne by the “retired soldier.” The focus is on the panegyrics published in the traditionally enemical countries — Sweden and Russia: “The Speech of the Retired Soldier Addressed to the King Gustav III on January 24, 1778” and “The Song to His Imperial Majesty Alexander I … at His Ascending to the Throne, from the Retired Soldier” (1801) accordingly. The protagonist of the Swedish composition participated in Karl XII’s campaigns, fought near Narva, was taken prisoner near Poltava, and after his return from Siberia in 1721, began to live as a hermit. The ghost of the king-soldier Gustav II visits the soldier-hermit, foretells the fortunate reign of his namesake, and asks the former to pass the news on to Gustav III. While “The Speech” emphasizes that the time of Swedish disgrace has continued very long, the Russian “Song,” while recalling the “golden time” of Catherine II, is more optimistic. The short period of grief has passed; therefore, the soldier is vigorous and lively. Catherine’s and Alexander’s reigns are separated by several years, while the rift between the eras of Gustav II and Gustav III is one and a half century. For the author of “The Song,” the fact that the disgraceful epoch has not lasted long, forms the specific feature of contemporary Russian history. By comparing Russian and Swedish texts, this idea becomes especially conspicuous.